2022
DOI: 10.1155/2022/8264958
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hypertensive Disease in the First Trimester of Pregnancy: Risk Models and Analysis of Serum D-dimer Levels Combined with Plasma Pregnancy-Associated Protein A, Free β-Subunit of Human Chorionic Gonadotropin, and Fetal Nuchal Translucency

Abstract: We aimed to investigate the predictive ability of serum levels of D-dimer (DD) in the first trimester for the occurrence of hypertensive disorders of pregnancy (HDP). In this retrospective, case-cohort study, we measured the levels of DD, plasma pregnancy-associated protein A (PAPP-A), and free β-subunit of human chorionic gonadotropin (free β-hCG) and analyzed fetal nuchal translucency (NT) in 150 healthy gravidas, 126 cases of gestational hypertension (GH), 53 cases of preeclampsia (PE), and 41 cases with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, another study revealed a positive correlation between birth weight and PAPP-A levels in early pregnancy 8 . In these studies, no adjustments were made for smoking and maternal weight 9 . In another study 1622 pregnant women who were in IUGR and examined the levels of PAPP-A, free β-hCG, and fetal NT between the groups, and they found that only the PAPP-A level was 3.3 times significant in detecting IUGR below 0.50 MoM 10 .…”
Section: Discussionmentioning
confidence: 99%
“…However, another study revealed a positive correlation between birth weight and PAPP-A levels in early pregnancy 8 . In these studies, no adjustments were made for smoking and maternal weight 9 . In another study 1622 pregnant women who were in IUGR and examined the levels of PAPP-A, free β-hCG, and fetal NT between the groups, and they found that only the PAPP-A level was 3.3 times significant in detecting IUGR below 0.50 MoM 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the sensitivity and specificity of beta HCG in predicting pregnancy induced hypertension was found as 83.3% and 96.9% respectively. (7) The human beta-hCG is with lipid structure that is present in trophoblast and various malignant tumors as a glycoprotein. The function of Human placenta is that it synthesizes hormones, protein, and glycoprotein hormones throughout gestation.…”
Section: Introductionmentioning
confidence: 99%